PENERAPAN NILAI-NILAI ASWAJA DALAM KEGIATAN KEAGAMAAN DI SDI NURUL BAYAN SUMENEP - Noor Alfi Fajriyani; Rosichin Mansur; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
The elementary level education is education that can be regarded as the main education for students to start learning and character building in children. Based on temporary observations at the Nurul Bayan Islamic Elementary School Sumenep, it is one of the private educational institutions that has four religious activity programs as a forum for character development for students. This research is located in Sumenep Madura. It is used three methods of data collection, namely; observation, interview and documentation. In the implementation of the program of religious activities, it is instilled aswaja values as the identity of the school. Four elements of aswaja values are embedded in the program of religious activities, namely the form of the value of tawassuth, tawazun, I'tidal, and amar ma'ruf nahi munkar. These four elements are applied to the container for the religious activity program. The religious activity programs at SDI Nurul Bayan are four program activities. They are daily, weekly, monthly, and yearly religious activity programs..Kata kunci: Nilai-Nilai Aswaja, Kegiatan Keagamaan, Tradisi Amaliyah NU